2016
DOI: 10.1128/jvi.00549-16
|View full text |Cite
|
Sign up to set email alerts
|

Robust Lys63-Linked Ubiquitination of RIG-I Promotes Cytokine Eruption in Early Influenza B Virus Infection

Abstract: Influenza

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
27
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 27 publications
(27 citation statements)
references
References 52 publications
0
27
0
Order By: Relevance
“…Phosphorylation of another site on NS1, Thr80, has also been reported to disrupt NS1 binding affinity with RIG-I (103). Similar to IAV, the IBV non-structural NS protein (NS1-B) has recently been described as inhibiting RIG-I ubiquitination, which involves TRIM25-NS1 C-terminal effector domain interaction and the RIG-I/TRIM25/ NS1-B complex formation (104). By contrast, the protease NS3-4A of HCV functions differently, rather than inhibiting TRIM25, it is thought to target the E3 ligase Riplet.…”
Section: Modulation Of the Ptmsmentioning
confidence: 99%
“…Phosphorylation of another site on NS1, Thr80, has also been reported to disrupt NS1 binding affinity with RIG-I (103). Similar to IAV, the IBV non-structural NS protein (NS1-B) has recently been described as inhibiting RIG-I ubiquitination, which involves TRIM25-NS1 C-terminal effector domain interaction and the RIG-I/TRIM25/ NS1-B complex formation (104). By contrast, the protease NS3-4A of HCV functions differently, rather than inhibiting TRIM25, it is thought to target the E3 ligase Riplet.…”
Section: Modulation Of the Ptmsmentioning
confidence: 99%
“…FLUBV undergoes uncoating after fusion of viral and endosomal membranes, but many of the details of FLUBV uptake and uncoating are still unknown. Interestingly, cellular immune responses to FLUBV infection differ from those to FLUAV infection (Jiang et al, 2016;Mäkelä et al, 2015). Therefore, it is possible that host processes involved in other steps of FLUBV infection also differ, as suggested by the discordant importance of EPS8 for FLUAV and FLUBV.…”
Section: Discussionmentioning
confidence: 99%
“…During the infection, viruses are recognized by pattern recognition receptors, the innate response is triggered, and interferons (IFNs) are secreted to limit early viral proliferation [6]. This identification leads to an appropriate antiviral response and to the activation of inflammatory response and adaptive immune responses [7]. While the reasons for the limited host range of IBV remain unclear, one of explanations is that the interaction between IBV and the innate immune system imbues the virus with distinct characteristics, such as the role of ISG15, a typical interferon-induced antiviral gene for the innate immune response [8,9].…”
mentioning
confidence: 99%
“…Existing studies describe the production of host cytokines, including IFNs, IFN-stimulated genes (ISGs), and proinflammatory cytokines against influenza virus infection, as integral parts of the process of the cellular antiviral response [10][11][12][13]. We have also reported that type I IFNs, ISGs, and proinflammatory cytokines can be induced by IBV virions at the early stage of virus infection [7,14].The interaction between influenza virus infection and the host anti-viral response has been investigated in depth [15,16], and the regulatory mechanism of IBV infection is also under investigation. Previous research has already shown that IBV ribonucleoprotein rapidly activates TLR signaling pathways [14].…”
mentioning
confidence: 99%
See 1 more Smart Citation